Clinical Outcomes of Ventilator-Associated Pneumonia in Critically Ill Patients Admitted to Intensive Care Unit - Muzamil Mehmood, Shah Zaman Gul, Faisal Iqbal, Muhammad Shabeer Khan, Abdul Kabir, Saba Gul, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Ventilator-associated pneumonia is a frequent hospital-acquired infection among critically ill patients receiving invasive mechanical ventilation. It is associated with prolonged ICU stay, longer duration of mechanical ventilation, antimicrobial resistance, septic shock and increased mortality. Timely recognition of VAP and evaluation of its outcomes are essential to improve ICU care. Objective: To determine the clinical outcomes of ventilator-associated pneumonia in critically ill patients admitted to the intensive care unit. Methods: This prospective observational cohort study was conducted in the Intensive Care Unit of Lady Reading Hospital, Peshawar, from April 2023 to August 2023. A total of 75 mechanically ventilated adult patients were enrolled through non-probability consecutive sampling and followed during ICU admission. Patients admitted with pneumonia, ventilation duration <48 hours and incomplete records were excluded. Demographic data, comorbidities, VAP status, microbiological findings, APACHE II score, duration of mechanical ventilation, ICU stay, septic shock, acute kidney injury, vasopressor requirement and ICU mortality were recorded. Data were analyzed using SPSS version 25. Effect sizes were reported as mean differences or odds ratios with 95% confidence intervals. A p-value <0.05 was considered statistically significant. Results: Out of 75 mechanically ventilated ICU patients, VAP was diagnosed in 28 (37.3%) patients, while 47 (62.7%) did not develop VAP. Late-onset VAP was more frequent than early-onset VAP [18 (64.3%) vs 10 (35.7%)]. The most common organisms were Acinetobacter baumannii, Klebsiella pneumoniae and Pseudomonas aeruginosa. Patients with VAP had longer duration of mechanical ventilation, prolonged ICU stay, higher septic shock, greater vasopressor requirement and increased ICU mortality compared with non-VAP patients. ICU mortality was 50.0% in the VAP group and 25.5% in the non-VAP group (OR = 2.92, 95% CI: 1.10–7.72, p = 0.031). APACHE II score was independently associated with ICU mortality (AOR = 1.12, 95% CI: 1.02–1.24, p = 0.021). Mortality was also higher among patients with multidrug-resistant organisms. Conclusion: Ventilator-associated pneumonia was associated with poor clinical outcomes among critically ill ICU patients. VAP patients had longer ventilation duration, prolonged ICU stay, higher septic shock, increased vasopressor support and greater ICU mortality. Baseline severity of illness and multidrug-resistant infection further contributed to mortality risk. Strict infection-control practices, ventilator-care bundles, early diagnosis and culture-guided antibiotic therapy are essential to reduce the burden of VAP in ICU settings. Keywords: Ventilator-associated pneumonia, ICU, mechanical ventilation, clinical outcomes, mortality, septic shock, multidrug resistance, APACHE II.